The continuing story of nutritional supplements and doping infractions - de Hon, O.; Coumans, B. (British Journal of Sports Medicine, 2007)
Nutritional supplements can be a source of positive doping cases as some supplements contain prohibited substances without showing this on their label. This problem has existed for some time and has been extensively studied in the past 8 years. The sport of tennis has played a particular role in this problem because of some peculiar doping cases within its community.